Relationships between family background and family strengths with children's social competence - Arshat, Zarinah; Baharudin, Rozumah; Juhari, Rumaya; Abu Talib, Mansor (Universiti Putra Malaysia Press, 2009)
This study aims to determine the relationships between family background (parental age, parental education, number of children, family monthly income) and family strengths with children’s social competence. A sample of 200 parents completed parent and child measures in a structured questionnaire. The results showed that all the variables for the family background were not significantly related to children’s social competence. Families who had higher levels of togetherness and utilized more respectful communication had children who displayed higher levels of social competence. The findings imply that children with higher levels of social competence come from families with higher level of family strengths.